Analisis Yuridis Tentang Tindak Pidana Menyatakan Diri Mempunyai Kekuatan Gaib - Pratama, Raka Indra (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
The problem in this study is regarding the legal understanding of the crime of declaring oneself as having supernatural powers. This study aims to determine and analyze the legal provisions regarding the crime of declaring oneself as having supernatural powers, along with the intent and purpose of the legal provisions being made. The type of research uses normative legal research, by analyzing Article 252 of Law Number 1 of 2023 concerning the Criminal Code. The results of the study reveal that the crime of declaring oneself as having supernatural powers is a crime that does not need to be proven whether supernatural powers are real or exist or not but is focused on the act of declaring oneself as having supernatural powers, the supernatural act is intended to cause illness or suffering, with the threat of imprisonment or a fine. The intent and purpose of this article are to overcome the act of taking the law into one's own hands by the community, especially to avoid persecution carried out against someone who opens a black magic or shamanism practice.